2014
DOI: 10.1017/s0950268814001332
|View full text |Cite
|
Sign up to set email alerts
|

First norovirus outbreaks associated with consumption of green seaweed (Enteromorpha spp.) in South Korea

Abstract: In February 2012, an outbreak of gastroenteritis was reported in school A; a successive outbreak was reported at school B. A retrospective cohort study conducted in school A showed that seasoned green seaweed with radishes (relative risk 7·9, 95% confidence interval 1·1-56·2) was significantly associated with illness. Similarly, a case-control study of students at school B showed that cases were 5·1 (95% confidence interval 1·1-24·8) times more likely to have eaten seasoned green seaweed with pears. Multiple n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 24 publications
0
12
0
1
Order By: Relevance
“…Park et al. () indicated potential causes such as person‐to‐person transmission and water‐borne transmission (for example, contaminated water during farming or manufacturing), whereas Sakon et al. () noted that contamination most likely occurred during manufacturing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Park et al. () indicated potential causes such as person‐to‐person transmission and water‐borne transmission (for example, contaminated water during farming or manufacturing), whereas Sakon et al. () noted that contamination most likely occurred during manufacturing.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the source of norovirus contaminated seaweed can be difficult to pinpoint. Park et al (2015) indicated potential causes such as person-to-person transmission and water-borne transmission (for example, contaminated water during farming or manufacturing), whereas Sakon et al (2018) noted that contamination most likely occurred during manufacturing. Park, Kang, and Ha (2016) observed that the antimicrobial effects of vinegar against pathogens such as norovirus resulted in about a 1-log reduction in green laver during cold storage.…”
Section: 323mentioning
confidence: 99%
“…Human activity influences the presence and prevalence of human norovirus in the aquatic environment [ 40 ], and outbreaks caused by waterborne viruses have caused serious health and socio-economic impacts [ 41 ]. Although the presence of HNoVs in clams has been widely reported [ 9 , 42 46 ], HNoV monitoring in coastal environments is relatively limited [ 2 , 17 , 24 ]. In this study, we investigated the prevalence, seasonal dependence, and genotypic diversity of both NoV GI and GII in four different estuaries (clam fisheries) and their inflow streams, which were in the vicinity of human dwellings in South Korea.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, another norovirus outbreak associated with consumption of green seaweed that was eaten unheated with vinegar seasoning was reported in South Korean schools. 8 However, outbreaks due to shredded, dried, laver seaweed processed for long-term preservation are unprecedented. As such, the current events provide several implications for preventing future norovirus outbreaks.…”
Section: Multiple Norovirus Outbreaks Due To Shredded Dried Laver Smentioning
confidence: 99%